Analisis Kebijakan Dividen: Index CGPI sebagai Variable Moderasi - Wulan Destiana Lestari Lasiman; Ayu Lestari; Sela Paramita Yuliartini (Owner : Riset dan Jurnal Akuntansi, 2022)
This study aims to empirically examine the effect of leverage, profitability, liquidity, the CGPI index in moderating, and the CGPI index in moderating dividend policy. This study uses quantitative methods with sample criteria are companies that do not consistently follow the CGPI ranking and companies that do not consistently distribute dividends. The object of research is a company registered in CGPI with data sources obtained at IDX and IICG. The results of this study, firstly, the effect of leverage on dividend policy has a significant positive effect, the high debt of the company causes the holding of the company's dividends. Second, the effect of profitability on dividend policy does not have a significant effect, because profitability is used for business expansion. Third, the effect of liquidity on dividend policy has an insignificant effect, because liquidity is used to pay off term debt with a period of less than one year. Fourth, the CGPI index as a moderating variable, the effect of leverage on dividend policy, cannot be moderated by the CGPI index, because good or bad reputation is not a guarantee if the company will give dividends to investors, because the company's main priority is paying off debt. Fifth, the CGPI index as a moderating variable, the influence of profitability on dividend policy, cannot be moderated by the CGPI index, because it is not always bad news for investors even if the company has a good reputation. Sixth, the CGPI index as a moderating variable, the influence of liquidity on dividend policy, cannot be moderated by the CGPI index, because high liquidity is not able to guarantee the amount of dividends distributed is getting bigger even if the company has a good reputation.